PENGARUH STRATEGI DIFERENSIASI DAN JIWA KEWIRAUSAHAAN TERHADAP LOYALITAS KONSUMEN INDUSTRI ROTI - Siti Ahdina Saadatirrohmi; Rismawati (Nusantara Hasana Journal, 2024)
Competitive competition in maintaining customer loyalty is crucial for business sustainability. Differentiation strategies are carried out by companies to create competitive advantages through differences in products and services offered, while entrepreneurial spirit includes the spirit of innovation, creativity, and adaptation to market changes. This study aims to analyze the effect of differentiation strategy and entrepreneurial spirit on consumer loyalty in the bakery industry in Babakan Village. This research uses a quantitative method with a survey approach through distributing questionnaires to 96 respondents who were selected incidentally. The data obtained were analyzed using multiple linear regression to test the effect of independent variables (differentiation strategy and entrepreneurial spirit) on the dependent variable (consumer loyalty). The results showed that both differentiation strategy and entrepreneurial spirit have a significant influence on customer loyalty. The differentiation strategy with a coefficient value of 0.5017 and the entrepreneurial spirit with a coefficient value of 0.5762 contribute positively to increasing customer loyalty. The F test conducted also indicates that simultaneously, the two independent variables significantly affect customer loyalty.